Branding Bawaslu dalam Meningkatkan Kepercayaan Publik terhadap Pengawasan Pemilu: Studi Kasus pada Strategi Branding Bawaslu Kabupaten Ngada - Johanis Aldian Sina Redo; Veki Edizon Tuhana; Henny L.L. Lada (Jurnal Ilmiah Teknik Informatika dan Komunikasi, 2026)
This research aims to identify the branding strategies implemented by Bawaslu Ngada Regency in enhancing public trust in election supervision. This study employs a constructivism paradigm with a qualitative approach and case study method, with data collection through in-depth interviews, social media observations, and documentation involving the Head of Bawaslu Ngada, Public Relations Officer, and Bawaslu Ngada staff. Data analysis uses the Miles and Huberman model with data validity tested through source and method triangulation, and applies David Aaker's Brand Equity theory encompassing dimensions of brand awareness, brand associations, perceived quality, and brand loyalty. The research findings reveal that Bawaslu Ngada Regency implements five main strategies in building brand equity: branding through mass media and social media (Facebook and Instagram); face-to-face community activities through the "Healthy Friday" program and citizen forums; formation and empowerment of participatory supervisors through the Participatory Supervisor Cadre School (SKPP); political education through the "Bawaslu Goes to School" program; and opening multi-channel information services through offices, official websites, PPID, and the SIWASLU application. These strategies successfully increased institutional visibility and created positive associations with values of public participation, transparency, and accountability, although implementation still faces challenges including minimal communication appeal, limited budget and human resources, digital divide, and inconsistent implementation at various levels.